Impact of gamma irradiation alone or in combination with Trichogramma spp. on the life stages of Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) - Esraa M. Abdel Halim; Sayeda S. Ahmed; Mona B. R. El-Mandarawy; Magda H. Naroz (Egyptian Journal of Biological Pest Control)
Abstract Background The study evaluated the effects of gamma irradiation alone and in integration with the egg parasitoid species, Trichogramma evanescens (Westwood) and Trichogrammatoidea bactrae (Nagaraja) (Hymenoptera: Trichogrammatidae) on controlling various developmental stages of the stored product pest, Angoumois grain moth, Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae). Results The results indicated that the increasing of the irradiation doses from 50 to 150 Gy caused significantly reduction in S. cerealella egg hatch. This reduction in the hatchability percentage reached to 99.10% at the dose of 150 Gy. After 7 days of irradiating S. cerealella eggs, the hatchability–dose response revealed that the sublethal dose (LD25), the median lethal dose (LD50) and the lethal dose (LD90) were 58.32, 79.73 and 144.41 Gy, respectively. Gamma irradiation doses adversely impacted S. cerealella development, significantly reducing both adult emergence and egg hatch rates. The 2nd instar of S. cerealella larvae inside the wheat grains was more tolerant than the 4th instar larvae. However, the pupal stage exhibited greater tolerance to irradiation compared to larval stage. A dose of 400 Gy resulted in a 4.75% adult emergence rate for 2nd instar larvae, while 300 Gy completely prevented adult emergence in 4th instar larvae. Near-complete sterility for pupae required a dose of 600 Gy. Furthermore, LD25 and LD50 values of radiation-treated S. cerealella eggs < 24 h were significantly reduced the preference of Trichogramma spp. in the consecutive generations (P1, F1 and F2). Additionally, irradiating 7-day-old (pupal stage) of T. evanescens and T. bactrae enabled resistance in the F1 and F2 generations at the LD25 dose, whereas irradiating 1-, 3- and 5-day-old parasitoids completely inhibited emergence in their generations. Conclusion It was concluded that integration of the gamma irradiation with Trichogramma spp. provides an effective alternative for controlling the stored pest S. cerealella. The study also identifies the optimal irradiation stages for parasitoids, enhancing integrated pest management strategies.